Properties of cellulose nitrates produced by nitration of bacterial cellulose using mixed sulfuric-nitric acids - Gorbatova, P. A.; Korchagina, A. A.; Gismatulina, Yu. A.; Shavyrkina, N. A.; Budaeva, V. V. (Proceedings of Universities. Applied Chemistry and Biotechnology, 2024)
The study set out to investigate the chemical functionalization of bacterial cellulose as an alternative means of satisfying the high demand for nano-sized cellulose nitrates. Using a Medusomyces gisevii Sa-12 symbiotic culture as a microbial producer, bacterial cellulose having a polymerization degree of 3950 was obtained on a synthetic glucose medium. Nitration was carried out using mixed sulfuric-nitric acids differing in their water content, followed by stabilization of the synthesized bacterial cellulose nitrates. Subject to a varying water content (14, 16 and 20 %) in the nitrating mixture, the obtained bacterial cellulose nitrates exhibited a nitrogen mass content of 8.68–11.56 %, a solubility in alcohol-ether mixture of 16.5–91.0 % and a viscosity of 32–255 mPa×s. The bacterial cellulose nitrate fibers were shown to have a nanoscale nature. Coupled thermogravimetric and differential thermal analyses revealed the bacterial cellulose nitrates to have a high chemical purity and energy content. FTIR spectroscopy confirmed the high quality of the bacterial cellulose based on the presence of basic functional groups characteristic of conventional cellulose: 3371, 2943, 1633, 1428, 1371, 1163, and 1112 cm -1 . According to their infrared spectra, the detected basic functional groups corroborate that the synthesized products are low-substituted cellulose nitrate esters: 1660–1643, 1282-1276, 847–837, 752–749, and 691–690 cm -1 . The relationship between the properties of the synthesized bacterial cellulose nitrates and the water mass content in mixed sulfuric-nitric acids is shown to have a complex nature.